The green side of productivity An international classification of green and brown occupations - Scholl, Nathalie (OECD Publishing, 2023)
This paper describes the methodology used for crosswalking occupation-based measures of Green ("environmentally friendly") and Brown ("polluting") jobs from the Standard Occupational Classification (SOC) system to the International Standard Occupation Classification (ISCO) 08 at the most detailed (4-digit) level. The original, task-based Greenness scores by Vona et al. (2018) are provided at the 8-digit SOC level, and the industry-based Brownness measures are provided in 6-digit SOC. Crosswalking these measures requires several choices in terms of weighting and aggregating, which this paper describes in detail. The robustness of the resulting measures to the different weighting options and underlying assumption is tested using Linked Employer-Employee data from Portugal. An empirical application to the Productivity-Greenness link at the firm level shows the robustness of this link to different weighting choices, and confirms that all of the different measures derived are consistent in measuring the Greenness of jobs
Keywords: Science and Technology; Economics